Wnt Gene Expression During Early Embryogenesis in the Nymphalid Butterfly Bicyclus anynana - Holzem, Michaela; Braak, Nora; Brattström, Oskar; McGregor, Alistair P.; Breuker, Casper J. (Frontiers in Ecology and Evolution, 2019)
The Wnt signalling pathway is an important developmental pathway involved in many cellular processes such cell cycle, proliferation and differentiation. Wnt ligands are released by source cells and signal to target cells by binding to the Frizzled receptor family and triggering changes in downstream target gene expression. Wnt signalling evolved early in animal evolution and an early expansion in the repertoire of Wnt ligands, which is thought to achieve specificity and robustness is present. There are 13 known Wnt ligand families in metazoans but little is known about these ligands in many animal lineages. Understanding the roles of these important signalling molecules in a wider range of animals is crucial to understand the regulation and evolution of cell fate during development and how this can lead to diversification. Here, we analysed the Wnt repertoire among lepidopterans, where these ligands are understudied compared to other insect orders. To be able to explore Wnt gene roles during butterfly embryogenesis we established a staging system for the well-established butterfly model, Bicyclus anynana, and assayed the expression pattern of all eight lepidopteran Wnt genes during early butterfly development, compared to their homologues in Drosophila melanogaster and Tribolium castaneum. We detected expression of Wnt1, Wnt10 and WntA in segmental stripes as well as expression of Wnt7 in the nervous system. Overall, our study provides much needed new insights into butterfly embryogenesis and potential roles of Wnt genes in specifying cell fate in these animals as well as how this compares to other animals.